Kafalah al-Yatim dari Perspektif Hadis Nabi - Hamid, Rosmaniah (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2017)
An aspect of the Holy Prophet’s main concerns is kafālat al-yatῑm (orphan provision). The Prophet as uswah hasanah, has practiced and ordered that his people nurture orphans with their best care. In this respect, Muslims are obliged to take a good care of orphans and to support them with provision. How this orphan care should be performed, with reference to the instructions of the Prophet, is the subject to be reviewed in this article. The method applied is ma’an al-hadith, a method which seeks to analyze the meaning of the material contained by the hadith (matn) using a variety of analytical techniques. Through these methods, the author finds that the basic instructions given by the Prophet with regards to orphan care is closely related to motivation of conducting it, rules of orphan’s property management, and substantial profits earned by those who cares for orphans.